Immune Response to Bacteria: An Integrated Learning Module to Enhance Preclinical Students' Competency in Immunology - Niti Manglik; Ellen F. Dudrey; Dolgor Baatar; Janet F. Piskurich (Association of American Medical Colleges, 2017)
Introduction Medical students express frustration that they cannot assemble a comprehensive big picture of how the immune system responds to a microbe and that integration of basic science knowledge, especially across disciplines, with clinical knowledge is difficult. Yet medical student competency requires application of knowledge of immune mechanisms to inform diagnosis and treatment. Methods A diagram for immune response to extracellular microbes was previously published by MedEdPORTAL in 2011. This diagram has been updated here as a narrated audiovisual module with integrated histopathology. It contains a self-assessment quiz that tests students' understanding of the module followed by a clinical vignette that tests students' ability to apply the concepts in a clinical context. The module was published and usage was tracked via our learning management system. An in-class survey was conducted to gauge students' perceptions of the module. Results Eighty-two out of 102 (76%) first-year medical students used the module. Over 85% of survey participants felt that the module was a useful resource for learning and reviewing. More than 90% felt that the module helped them to understand the big picture and identify areas for further study. Discussion This module assembles a big picture of the immunologic mechanisms involved in a bacterial infection. It was created in response to requests and suggestions by preclinical medical students and used for first-year students during the first few weeks of their training in the basic sciences. This approach integrates multiple disciplines and facilitates students' learning and application of difficult concepts in immunology and pathology.